THE IMPACT OF FINANCIAL PERFORMANCE ON INVESTMENT OPPORTUNITY AND COMPANY VALUE IN INDONESIA’S CONSUMER-GOODS SECTOR - Jonathan, LCA Robin; Militina, Theresia (Archives of Business Research, 2019)
This study aimed to analyze and identify whether the company performance projected in the variables of liquidity, leverage, activity and profitability influenced investment opportunities and company value in the consumer goods sector listed in IPO in Indonesia (2013-2015). Along with the increasing population and improving economic conditions in Indonesia, public consumption is also increased. This boosts the sales of consumer goods industry sector, as well as improve the business prospects of the consumer goods sector. The sample taken was 37 entities, based on the number of listed companies up to the IPO 2015, consisting of 17 food and beverage subsector entities), cigarettes / tobacco (4 entities), pharmacy (9 entities), cosmetics & household necessities (4 entities), and household appliances (3 entities) during 2013-2015 financial statements. This study was a quantitative causality study between several variables using cross section data. This research used secondary data in the form of financial statements published on the Indonesia Stock Exchange, and academic literatures. The results showed that (1). The direct effect of company performance: CR, DA, and Tattoos had no significant effect on investment opportunities and ROA had a significant effect on investment opportunities. (2). Direct influence Company performance: CR, DA, and ROA had a significant effect on stock prices and Tattoos had no significant effect on stock prices. (3). Indirect influence, company performance: CA and DA had a significant effect on stock prices through investment opportunities and Tattoos, ROA did not significantly influence stock prices through investment opportunities.